Penerapan Metode Preference Selection Index (PSI) Dalam Menilai Kinerja Dosen Saat Pembelajaran Daring Dimasa New Normal - Neni Mulyani; Zulfi Azhar; Jeperson Hutahaean; Fitri Hadanyani; Indah Kurnia (Universitas Budi Darma, 2023)
The performance of lecture during brave learning has drastically decreased due to the lack of communivation between lectures and students. As a result of bold learning. Lecturers often do not do learning using zoom meetings but only provide material without explaining it. Then the risk that will arise for lecturers who do not provide student learning reports will result in students not being enthusiastic in lectures, so that they can be reviewed in an assessment of lecturer performance. Therefore a decision support system is made to facilitate the calculation process of all criteria for assessing lecturer performance. The purpose of this decision support system is to determine the criteria for a problem using the Preference Selection Index (PSI) method.